Land Titles, Investment, and Agricultural Productivity in Madagascar : A Poverty and Social Impact Analysis - Jacoby, Hanan; Minten, Bart (World Bank, Washington, DC, 2013)
This report examines the question of land titling in Madagascar, a country where modern and informal tenure systems coexist and overlap to a significant extent. The report reviews three main arguments for land titling and their relevance for Madagascar in order to provide policy implications and evaluations. The first is that land titling serves as protection against expropriation. Second, titles may also facilitate land transactions. Last, that owning titled land improves access to formal credit or increases the volume of formal credit conditional on access. The report concludes that it is not obvious that expanded land titling, or community-based land registration, constitutes the best route to attaining distributional objectives, since wealth is increasing in landholdings. A cost benefit analysis based on the findings suggest that it would not be economical to expand the system of formal titling in rural Madagascar and that the three main arguments do not justify maintaining this system.